Negative electrode material and secondary battery

By combining carbon materials and silicon materials in the negative electrode material of lithium-ion batteries, and controlling the N/M ratio, the problem of volume expansion of silicon materials during the process of deintercalating lithium is solved, and the cycle life and rate performance of the battery are improved.

CN119340377APending Publication Date: 2025-01-21BTR NEW MATERIAL GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411853430.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The negative electrode materials of existing lithium-ion batteries, especially silicon materials, volume expansion during the deintercalation of lithium leads to structural damage and rapid attenuation of performance.

Method used

Anode materials including carbon materials and silicon materials are used. By controlling the particle size of the silicon material and the thickness of the carbon coating layer, the N/M ratio is adjusted within the range of 0.35 to 0.85 to reduce the formation and electrochemical sintering of lithium-silicon alloy.

Benefits of technology

Effectively alleviate the volume expansion of silicon materials, improve the circulation life and multiplier performance of the negative electrode materials, and improve the overall electrochemical performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340377A_ABST
    Figure CN119340377A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode material and a secondary battery. The negative electrode material comprises a carbon material and a silicon material, metal lithium is used as a reference electrode and a counter electrode, a negative electrode material is used as a working electrode, button type half-cell charging and discharging tests are carried out under a first charging and discharging condition and a second charging and discharging condition, the discharging cut-off voltage of the first charging and discharging condition is 0.005 V, the charging cut-off voltage of the first charging and discharging condition is 1.5 V, the discharging cut-off voltage of the second charging and discharging condition is 0.025 V, the charging cut-off voltage of the second charging and discharging condition is 1.5 V, and the charging cut-off voltage of the second charging and discharging condition is 1.5 V. A dQ / dV-V curve is obtained; a maximum value of a dQ / dV-V curve of a secondary battery in a range of 0.4 V to 0.5 V under a first charge / discharge condition is M, a maximum value of a dQ / dV-V curve of a secondary battery in a range of 0.4 V to 0.5 V under a second charge / discharge condition is N, M and N satisfying: # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to a negative electrode material and a secondary battery. Background Art

[0002] With the rapid development and widespread application of electric vehicles, the market has put forward higher requirements for the energy density and cycle life of lithium-ion batteries. The energy density of lithium-ion batteries mainly depends on the selection of electrode materials. The traditional mainstream negative electrode materials mainly include graphite, but the specific capacity of graphite negative electrode is close to the theoretical upper limit and it is almost difficult to increase it further. The theoretical capacity of silicon is about 4200 mAh / g. It has the advantages of high capacity, wide source, environmental friendliness, and moderate lithium insertion potential. It is generally considered to be one of the next generation of high specific energy candidate lithium-ion battery negative electrode materials. However, silicon expands significantly in volume during the process of lithium insertion and extraction, which can easily cause silicon particles to break and pulverize, thereby causing damage to the electrode structure, or causing problems such as repeated growth of the solid electrolyte interface (SEI) film, resulting in rapid degradation of the performance of the silicon negative electrode. Summary of the invention

[0003] In view of this, the present application provides a negative electrode material to solve at least one of the above problems.

[0004] To achieve the above-mentioned object, the present application provides a negative electrode material, the negative electrode material includes a carbon material and a silicon material; metallic lithium is used as a reference electrode and a counter electrode, and the negative electrode material is used as a working electrode, and a button half-cell charge and discharge test is performed under a first charge and discharge condition and a second charge and discharge condition, the discharge cut-off voltage of the first charge and discharge condition is 0.005 V, and the charge cut-off voltage is 1.5 V, and the discharge cut-off voltage of the second charge and discharge condition is 0.025 V, and the charge cut-off voltage is 1.5 V, and a dQ / dV-V curve is obtained; under the first charge and discharge condition, the maximum value of the dQ / dV-V curve within 0.4 V to 0.5 V is M, and under the second charge and discharge condition, the maximum value of the dQ / dV-V curve within 0.4 V to 0.5 V is N, and M and N satisfy: In some possible implementations, the average particle size of the primary particles of the silicon material is 0.1 nm to 25 nm.

[0005] In some possible implementations, the size of a grain of the silicon material on the (111) crystal plane is less than or equal to 10 nm.

[0006] In some possible implementations, the negative electrode material has pores, and the porosity of the negative electrode material is 0.02% to 10%.

[0007] In some possible implementations, the average pore size of the negative electrode material is 0.5 nm to 50 nm.

[0008] In some possible implementations, the total pore volume of the negative electrode material is 0.001 cm 3 / g to 0.1 cm 3 / g.

[0009] In some possible implementations, the silicon material includes one or more of amorphous silicon, crystalline silicon, and a composite of crystalline silicon and amorphous silicon.

[0010] In some possible implementations, the silicon material includes one or both of silicon oxide and silicon alloy.

[0011] In some possible implementations, the morphology of the silicon material particles includes one or more of a dot shape, a sphere shape, an ellipsoid shape, and a flake shape.

[0012] In some possible implementations, the purity of the silicon material is greater than or equal to 99%.

[0013] In some possible implementations, the carbon material includes one or more of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers, graphene, and the like.

[0014] In some possible implementations, after removing the silicon material from the negative electrode material, the total pore volume is greater than or equal to 0.35 cm 3 / g.

[0015] In some possible implementations, after the silicon material is removed from the negative electrode material, the volume proportion of its mesopores in all its pores is greater than or equal to 65%, and the pore size of the mesopores is 2 nm to 50 nm.

[0016] In some possible implementations, after the silicon material is removed from the negative electrode material, the volume proportion of its micropores in all its pores is greater than or equal to 60%, and the pore size of the micropores is less than 2 nm.

[0017] In some possible implementations, after removing the silicon material from the negative electrode material, the specific surface area thereof is greater than or equal to 100 m 2 / g.

[0018] In some possible implementations, the median particle size Dv50 of the negative electrode material is 0.2 µm to 20 µm.

[0019] In some possible implementations, the specific surface area of ​​the negative electrode material is 0.1 m 2 / g to 10 m 2 / g.

[0020] In some possible implementations, the compacted density of the negative electrode material powder is 0.8 g / cm 3 Up to 1.5 g / cm 3 .

[0021] In some possible implementations, based on the mass of the negative electrode material, the mass proportion of carbon element in the negative electrode material is 10% to 60%.

[0022] In some possible implementations, based on the mass of the negative electrode material, the mass proportion of oxygen element in the negative electrode material is less than or equal to 5%.

[0023] In some possible implementations, the negative electrode material further includes a coating, which is located at the outermost layer of the negative electrode material, and the coating includes a carbonaceous material, and the carbonaceous material includes one or more of graphene, soft carbon, and hard carbon.

[0024] In some possible implementations, the coating includes a metal oxide layer, and the material of the metal oxide layer includes one or more of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide.

[0025] In some possible implementations, the coating includes a nitride layer, and the nitride layer includes one or more of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride, and carbon nitride.

[0026] In some possible implementations, the coating includes a polymer, and the polymer includes one or more of tannic acid, polyacrylonitrile, polyaniline, polyethylene glycol, polyvinyl alcohol, and asphalt.

[0027] In some possible implementations, the coating has a thickness of 0.1 nm to 100 nm.

[0028] The present application also provides a secondary battery, comprising the above-mentioned negative electrode material.

[0029] The present application controls the value of N / M within a preset range. On the one hand, the formation of crystalline lithium-silicon alloy generated by the reaction of silicon and lithium in the negative electrode material can be reduced, which is conducive to alleviating the volume expansion of silicon materials during the cycle, maintaining the stability of the structure of the negative electrode material, and improving the cycle life of the obtained secondary battery; on the other hand, it can avoid the electrochemical sintering of silicon negative electrodes during the lithiation / delithiation process to form large particles, which is conducive to improving the lithium deintercalation kinetics advantage of negative electrode materials, improving the rate performance and high-temperature storage performance of negative electrode materials, and thus improving the overall electrochemical performance of the obtained secondary battery. Since large-sized silicon particles in negative electrode materials are more likely to form lithium-silicon alloys, the degree of aggregation of large particles of silicon primary particles in negative electrode materials with N / M values ​​within a preset range is low, which is conducive to reducing the stress concentration and relative deformation of silicon particles; at the same time, since the uniform carbon coating can inhibit the formation of lithium-silicon alloys, the carbon coating uniformity of negative electrode materials with N / M values ​​within a preset range is high. Reasonable control of the N / M ratio can achieve a balance between cycle performance, expansion performance, rate performance and high-temperature performance, and improve the applicable range of negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during charging.

[0031] Figure 2 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during discharge.

[0032] Figure 3 This is the dQ / dV-V curve of the negative electrode material provided in Example 1 of the present application under the conditions of a discharge cut-off voltage of 0.005 V and a charge cut-off voltage of 1.5 V.

[0033] Figure 4 This is the dQ / dV-V curve of the negative electrode material provided in Example 1 of the present application under the conditions of a discharge cut-off voltage of 0.025 V and a charge cut-off voltage of 1.5 V.

[0034] Figure 5 This is a scanning electron microscope image of the morphology of the negative electrode material provided in Example 1 of the present application.

[0035] Figure 6 This is a scanning electron microscope image of the cross-section of the negative electrode material provided in Example 1 of the present application.

[0036] Figure 7 This is the X-ray diffraction analysis spectrum of the negative electrode material provided in Example 1 of the present application.

[0037] Figure 8 This is the cycle performance curve of the negative electrode material provided in Example 1 of the present application.

[0038] Fig. 9 This is the charge and discharge curve of the negative electrode material provided in Example 1 of the present application.

[0039] Main component symbols Electrode assembly 100 Positive electrode 101 Negative electrode 102 Isolation film 103. DETAILED DESCRIPTION

[0040] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0041] In view of the shortcomings of the existing technology, this application improves the preparation method of negative electrode materials and explores preparation methods with strong controllability of negative electrode material performance indicators, so as to achieve the purpose of accurately regulating the performance indicators of negative electrode materials and solve the problems of large silicon volume expansion, poor cycle performance and poor conductivity in existing negative electrode materials.

[0042] Based on this, an embodiment of the present application provides a secondary battery, comprising a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.

[0043] The outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it may also be a steel shell battery, an aluminum shell battery, etc.

[0044] See also Figure 1 and Figure 2 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103. The separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. When an electrolyte (not shown) is provided, when charging, refer to Figure 1 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode sheet 101, pass through the separator 103 through the electrolyte, reach the negative electrode sheet 102 and insert into the lattice of the negative electrode material. Figure 2 , active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode sheet 102, pass through the isolation membrane 103 through the electrolyte, reach the positive electrode sheet 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), generating electrons that travel from the negative electrode sheet 102 through the external circuit to the positive electrode sheet 101, and the reverse movement of the electrons forms an electric current that can be used by electrical appliances.

[0045] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.

[0046] Positive electrode The positive electrode sheet 101 includes a positive electrode current collector and a positive electrode material active layer provided on at least one surface of the positive electrode current collector. The positive electrode current collector may be made of aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode material active layer includes a positive electrode active material, and the positive electrode active material includes a compound that reversibly embeds and deintercalates lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO 2 ), lithium nickel manganese cobalt ternary materials (NCM), lithium manganese oxide (LiMn 2 O 4 ), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O 4 ) or lithium iron phosphate (LiFePO 4 ) at least one of.

[0047] The positive electrode material active layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode material active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.

[0048] The positive electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0049] Negative plate The negative electrode sheet 102 includes a negative electrode current collector and a negative electrode material active layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0050] The negative electrode material active layer includes a negative electrode material, and the negative electrode material includes a carbon material and a silicon material. Metal lithium is used as a reference electrode and a counter electrode, and the negative electrode material is used as a working electrode. A button half-cell charge and discharge test is performed under a first charge and discharge condition and a second charge and discharge condition. The discharge cut-off voltage of the first charge and discharge condition is 0.005 V, and the charge cut-off voltage is 1.5 V. The discharge cut-off voltage of the second charge and discharge condition is 0.025 V, and the charge cut-off voltage is 1.5 V. A dQ / dV-V curve is obtained; under the first charge and discharge condition, the maximum value of the dQ / dV-V curve within 0.4 V to 0.5 V is M, and under the second charge and discharge condition, the maximum value of the dQ / dV-V curve within 0.4 V to 0.5 V is N, and M and N satisfy: For example, It can be 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85 or any value within the range formed by any two of the above values.

[0051] The differential capacity curve dQ / dV-V is obtained by taking the first derivative of the charge and discharge capacity Q of the secondary battery to the voltage V, and then plotting it against the voltage V. dQ / dV can represent the capacity of the secondary battery within a unit voltage range, or the change in the capacity of the secondary battery within a small voltage change range. In the charge and discharge curve of the secondary battery, the higher the capacity under the voltage platform, the more capacity there is within a very small voltage fluctuation range, so it is represented as a characteristic peak on the dQ / dV-V curve, and dQ / dV has an extreme value at this time.

[0052] In the present application, under the discharge cut-off voltage conditions of the first charge and discharge conditions and the second charge and discharge conditions, the voltage range of 0.4V to 0.5V is the platform voltage formed by the silicon-lithium alloy, and the peak intensity within this voltage range can indicate the amount of silicon alloy formed under different charge and discharge conditions. Therefore, the N value and M value obtained under the above conditions can characterize the relative content of the lithium-silicon alloy formed in the negative electrode material.

[0053] The negative electrode material provided in the embodiment of the present application controls the value of N / M within a preset range. On the one hand, the reaction between the silicon material and lithium in the negative electrode material to form a crystalline lithium-silicon alloy can be appropriately reduced, which is conducive to alleviating the volume expansion of the silicon material during the cycle, and is conducive to maintaining the stability of the structure of the negative electrode material, and improving the cycle life of the obtained secondary battery; on the other hand, the degree of electrochemical sintering of the silicon material to form large particles during the lithiation / delithiation process can be reduced, which is conducive to improving the lithium deintercalation kinetics advantage of the negative electrode material, improving the rate performance and high-temperature storage performance of the negative electrode material, and then improving the overall electrochemical performance of the obtained secondary battery. Since large-sized silicon particles in the negative electrode material are more likely to form lithium-silicon alloys, the degree of electrochemical sintering of silicon materials to form large particles during the lithiation / delithiation process in the negative electrode material with an N / M value within a preset range is low, which is conducive to reducing the stress concentration and relative deformation of silicon material particles.

[0054] It can be understood that when the value of N / M is greater than 0.85, the negative electrode material may form more crystalline lithium-silicon alloys during the lithium insertion process, causing the negative electrode material to be subjected to huge stress during the lithium extraction process, exceeding the maximum pressure that the negative electrode material can withstand, causing the negative electrode material to be easily pulverized, resulting in the deterioration of the cycle performance and the first coulomb efficiency of the obtained secondary battery. Therefore, reasonable control of the range of N / M values ​​is conducive to achieving a balance between the cycle performance and kinetic performance of the negative electrode material, so that it can be widely used in secondary batteries. When the value of N / M is less than 0.35, there are too few crystalline lithium-silicon alloys and more amorphous lithium-silicon alloys. Due to the poor and unstable ionic conductivity of the amorphous lithium-silicon alloy, the rate performance and high temperature performance of the negative electrode material are poor. Therefore, reasonable control of the N / M ratio can achieve a balance between cycle performance, expansion performance, rate performance and high temperature performance, and improve the applicable range of negative electrode materials.

[0055] In some embodiments, in the negative electrode material of the present application, the silicon material is regarded as a matrix skeleton, and the carbon material is distributed along the skeleton of the silicon material; or the inside and outside of the silicon material are divided by the surface of the silicon material, and the carbon material partially distributed inside the silicon material extends to the outside of the silicon material as the carbon material accumulates, and then can be combined with more external coating layers and cover at least part of the surface of the silicon material. The silicon material has pores, and the carbon material dispersed around the silicon material can exist in the pores of the silicon material, but not completely fill them, so the negative electrode material also has pores and is a porous structure.

[0056] In another embodiment, in the negative electrode material of the present application, the carbon material is regarded as a matrix skeleton, and the silicon material is distributed along the skeleton of the carbon material; or the inside and outside of the carbon material are divided by the surface of the carbon material, and at least part of the silicon material is distributed inside the carbon material. The carbon material has pores, and at least part of the silicon material is distributed in the pores of the carbon material, but not completely filled, so the negative electrode material also has pores and is a porous structure.

[0057] In some embodiments, the silicon material may include amorphous silicon, crystalline silicon, or a composite of crystalline silicon and amorphous silicon. For example, the silicon material includes amorphous silicon, which expands isotropically during the lithium insertion process, which can reduce the collapse of pores in the negative electrode material, inhibit the rapid attenuation of the specific capacity of the negative electrode material, and is more conducive to improving the lithium insertion cycle performance of the negative electrode material.

[0058] In some embodiments, the silicon material may include at least one of silicon oxide, silicon alloy, and the like.

[0059] In some embodiments, the morphology of the silicon material particles may include at least one of a dot shape, a sphere shape, an ellipsoid shape, and a flake shape.

[0060] In some embodiments, the purity of the silicon material may be greater than or equal to 99%. High-purity silicon material is more conducive to Li-Si alloying with lithium, thereby improving the cycle performance of lithium-ion batteries prepared from negative electrode materials.

[0061] In some embodiments, the average particle size of the primary particles of the silicon material is 0.1 nm to 25 nm. For example, the average particle size of the primary particles of the silicon material can be 0.1 nm, 1 nm, 2.5 nm, 3 nm, 45 nm, 7 nm, 8 nm, 9 nm, 9.1 nm, 10 nm, 12 nm, 18 nm, 22 nm, 25 nm, or any value within the range formed by any two of the above values. Controlling the primary particles of the silicon material within the above range can control the primary particles of the silicon material to be at a suitable particle size, which is beneficial to reducing the stress concentration and relative deformation of the silicon particles after lithiation, avoiding pulverization and electrochemical sintering of the silicon material, and ensuring the structural stability of the silicon particles and alleviating the volume expansion of the silicon material.

[0062] In some embodiments, the size of the grains of the silicon material on the (111) crystal plane is less than or equal to 10 nm. For example, the size of the grains of the silicon material on the (111) crystal plane can be 0 nm, 1 nm, 2.5 nm, 3 nm, 3.7 nm, 3.8 nm, 3.9 nm, 4.1 nm, 4.2 nm, 4.9 nm, 5.5 nm, 7 nm, 8 nm, 9 nm, 10 nm, or any value within the range formed by any two of the above values. The size of the grains of the silicon material on the (111) crystal plane is calculated by X-ray diffraction analysis combined with the Scherrer formula. The size within the above range indicates that the grains of the silicon particles in the negative electrode material maintain a relatively stable size during the charge and discharge process and will not grow significantly, which is conducive to maintaining the cycle stability of the resulting secondary battery. When the calculated grain size of the silicon material on the (111) crystal plane is 0 nm, it means that the silicon material is amorphous silicon, that is, there is no crystalline silicon.

[0063] In some embodiments, the carbon material includes at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers, and graphene, etc. The carbon material is selected from the above materials, which can play a role in forming a conductive network with the silicon material.

[0064] In some embodiments, the negative electrode material further includes a coating layer, which is disposed on at least a portion of the surface of the negative electrode material particles and is arranged to inhibit the electrolyte from entering the interior of the negative electrode material. The coating layer is beneficial to improving the structural stability and conductivity of the negative electrode material. The uniform coating layer on the surface of the negative electrode material can inhibit the formation of lithium-silicon alloys, further improve the structural stability of the negative electrode material during the lithiation process, reduce the expansion rate of the negative electrode material, and is beneficial to the formation of a stable solid electrolyte film on the surface of the negative electrode material, and is also beneficial to the improvement of the conductivity of the negative electrode material, thereby improving the electrochemical performance of the negative electrode material.

[0065] In some embodiments, the coating layer may include a carbonaceous material, and the carbonaceous material may include at least one of graphene, soft carbon, hard carbon, and the like.

[0066] In some embodiments, the coating layer may include a metal oxide layer, and the material of the metal oxide layer may include at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide.

[0067] In some embodiments, the coating layer may include a nitride layer, and the material of the nitride layer may include at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride and carbon nitride.

[0068] In some embodiments, the coating may include a polymer, and the polymer includes one or more of tannic acid, polyacrylonitrile, polyaniline, polyethylene glycol, polyvinyl alcohol, asphalt, and the like.

[0069] In some embodiments, the thickness of the coating layer may be 0.1 nm to 100 nm. For example, the thickness of the coating layer may be 0.1 nm, 5 nm, 10 nm, 30 nm, 50 nm, 80 nm, 100 nm, or any value within the range formed by any two of the above values. The coating layer may reduce the solubility of the negative electrode material, thereby reducing the amount of gas produced by the reaction of the dissolved active substance with the electrolyte. Controlling the thickness of the coating layer within the above range is beneficial to maintaining the stability of the particle structure of the negative electrode material during the cycle, and can reduce the exposed active substance on the surface of the negative electrode material. Further, the thickness of the coating layer may be 1 nm to 50 nm, and further, the thickness of the coating layer may be 1 nm to 20 nm, which is beneficial to the rapid and reversible deintercalation of lithium ions.

[0070] In some embodiments, the coating layer may be a single-layer coating layer formed of the above-mentioned single material, or a coating layer formed by a combination of the above-mentioned multiple materials, or a multi-layer coating layer formed of a single material, or a multi-layer coating layer formed of multiple materials, etc. The layer structure of the coating layer can be selected according to actual needs. It can be understood that when the coating layer is a multi-layer coating structure, the density is higher.

[0071] In some embodiments, the porosity of the negative electrode material is 0.02% to 10%. For example, the porosity of the negative electrode material can be 0.02%, 0.1%, 1%, 2%, 4%, 5.6%, 7.5%, 7.8%, 8.1%, 9.2%, 9.9%, 10%, or any value within the range formed by any two of the above values. The porosity of the negative electrode material within the above range indicates that the negative electrode material has sufficient pores to provide a buffer space for the expansion of the silicon material, which is beneficial to reduce the expansion effect of the silicon material.

[0072] In some embodiments, the average pore size of the negative electrode material is 0.5 nm to 50 nm. For example, the average pore size of the negative electrode material can be 0.5 nm, 1 nm, 1.5 nm, 3 nm, 5 nm, 7 nm, 8 nm, 9 nm, 10 nm, 15 nm, 18 nm, 25 nm, 35 nm, 40 nm, 50 nm, or any value within the range formed by any two of the above values. The pores in the negative electrode material having the above-mentioned average pore size range can promote the filling of the carbon material in the pores, while reserving a certain amount of pore space to provide a buffer space for the expansion of the silicon material, which is beneficial to reduce the expansion effect of the silicon material.

[0073] In some embodiments, the total pore volume of the negative electrode material is 0.001 cm 3 / g to 0.1 cm 3 / g. For example, the total pore volume of the negative electrode material can be 0.001 cm 3 / g, 0.002 cm 3 / g, 0.006 cm 3 / g, 0.007 cm 3 / g, 0.008 cm 3 / g, 0.009 cm 3 / g, 0.010 cm 3 / g, 0.015 cm 3 / g, 0.050 cm 3 / g, 0.070 cm 3 / g, 0.085 cm 3 / g, 0.1cm 3 / g or any value within the range formed by any two of the above values. Controlling the total pore volume of the negative electrode material within the above range is conducive to making the negative electrode material have sufficient pores, providing a buffer space for the expansion of the silicon material, and is conducive to reducing the expansion effect of the silicon material.

[0074] In some embodiments, the median particle size Dv50 of the negative electrode material is 0.2 µm to 20 µm. For example, the median particle size Dv50 of the negative electrode material can be 0.2 µm, 1 µm, 3 µm, 5 µm, 5.5 µm, 6 µm, 7 µm, 8 µm, 10 µm, 13 µm, 15 µm, 18 µm, 20 µm, or any value within the range formed by any two of the above values. Controlling the median particle size of the negative electrode material within the above range is beneficial to improving the cycle performance of the negative electrode material. The median particle size Dv50 represents the particle size corresponding to when the volume cumulative particle size distribution percentage reaches 50%.

[0075] In some embodiments, the specific surface area of ​​the negative electrode material is 0.1 m 2 / g to 10 m 2 / g. For example, the specific surface area of ​​the negative electrode material can be 0.1 m 2 / g, 0.8 m 2 / g, 1.5 m 2 / g, 2.2 m 2 / g, 2.8 m 2 / g, 3 m 2 / g, 3.3 m 2 / g, 3.5 m 2 / g, 3.7 m 2 / g, 5 m 2 / g, 7 m 2 / g, 9 m 2 / g, 9.8 m 2 / g, 10 m 2 / g or any value within the range formed by any two of the above values. When the specific surface area of ​​the negative electrode material is large, the SEI film on the surface of the negative electrode material will consume excessive lithium salts, and the volume effect is likely to cause electrical separation between particles, resulting in a decrease in the reversible capacity and coulomb efficiency of the battery. Therefore, the specific surface area of ​​the negative electrode material in this embodiment is small, which is conducive to improving the capacity of the first discharge ratio and the first coulomb efficiency of the battery.

[0076] In some embodiments, the powder compaction density of the negative electrode material is 0.8 g / cm 3 Up to 1.5 g / cm 3 For example, the compacted density of the negative electrode material powder can be 0.8 g / cm 3 , 1.02 g / cm 3 , 1.05 g / cm3 , 1.1 g / cm 3 , 1.2 g / cm 3 , 1.21 g / cm 3 , 1.23 g / cm 3 , 1.4 g / cm 3 , 1.5 g / cm 3 Or any value within the range formed by any two of the above values. Controlling the compaction density of the negative electrode material powder within the above range helps to reduce the diffusion path of lithium ions in the negative electrode material, thereby improving the rate performance of the battery.

[0077] In some embodiments, based on the mass of the negative electrode material, the mass proportion of carbon in the negative electrode material is 10% to 60%. For example, the mass proportion of carbon in the negative electrode material can be 10%, 20%, 32%, 35%, 38%, 40%, 42%, 48%, 55%, 60%, or any value within the range composed of any two of the above values. The carbon element in the negative electrode material mainly comes from the carbon material on the silicon material skeleton and the carbon material formed on the surface of the silicon material. The mass proportion of carbon is controlled within the above range, indicating that the negative electrode material is filled with enough carbon material, which is beneficial to improve the conductivity. At the same time, a suitable amount of carbon layer is formed on the surface, which is beneficial to maintain a good interface resistance of the negative electrode material and improve the capacity of the secondary battery obtained.

[0078] In some embodiments, based on the mass of the negative electrode material, the mass proportion of oxygen in the negative electrode material is less than or equal to 5%. For example, the mass proportion of oxygen in the negative electrode material can be 5%, 4%, 3.2%, 3%, 2.8%, 2.5%, 2.3%, 1.5%, 1.4%, 1%, or any value within the range formed by any two of the above values. The oxygen in the negative electrode material can be derived from silicon material (such as silicon-oxygen precursor), and controlling the mass proportion of oxygen in the negative electrode material within the above range is conducive to forming a silicon material rich in pores.

[0079] In some embodiments, 150 mL of 20% by mass HF acid solution was added dropwise to 10 g of negative electrode material under stirring to produce SiF 4 and H 2 Gas is generated and heat is released. After no gas is generated, the supernatant acid solution is removed by centrifugation. 150 mL of 20% mass fraction HF acid solution is added to the negative electrode material again. After stirring for 12 hours, the supernatant acid solution is removed by centrifugation again. Then, the negative electrode material is washed with pure water until it is neutral and dried to obtain the negative electrode material after removing the silicon material, that is, the carbon material in an ideal state.

[0080] In some embodiments, after removing the silicon material from the negative electrode material, the total pore volume is greater than or equal to 0.35 cm 3 / g. For example, the total pore volume of the negative electrode material after removing the silicon material can be 0.35 cm 3 / g, 0.43 cm 3 / g, 0.45 cm 3 / g, 0.50cm 3 / g, 0.53 cm 3 / g, 0.56 cm 3 / g, 0.75 cm 3 / g or any value within the range formed by any two of the above values.

[0081] In some embodiments, after the silicon material is removed from the negative electrode material, the volume percentage of the mesopores in all the pores is greater than or equal to 65%, and the pore size of the mesopores is 2 nm to 50 nm. For example, after the silicon material is removed from the negative electrode material, the volume percentage of the mesopores can be 65%, 70%, 78%, 80%, 85%, 86%, 89%, 90%, or any value within the range of any two of the above values.

[0082] In some embodiments, after the silicon material is removed from the negative electrode material, the volume proportion of the micropores in all the pores is greater than or equal to 60%, and the pore size of the micropores is less than 2 nm. For example, the volume proportion of the micropores in the negative electrode material after the silicon material is removed can be 60%, 65%, 70%, 78%, 80%, 85%, 86%, 89%, 90%, or any value within the range formed by any two of the above values.

[0083] In some embodiments, after removing the silicon material from the negative electrode material, the specific surface area thereof is greater than or equal to 100 m 2 / g. For example, the specific surface area of ​​the negative electrode material after removing the silicon material can be 100 m 2 / g, 300 m 2 / g, 500 m 2 / g, 800 m 2 / g、1000m 2 / g, 1300 m 2 / g, 1500 m 2 / g, 1700 m 2 / g, 2000 m 2 / g or any value within the range formed by any two of the above values.

[0084] The negative electrode material active layer may also include a binder to bind the negative electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the binding force between the negative electrode material active layer and the negative electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc.

[0085] The negative electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0086] Isolation film The isolation membrane 103 includes a membrane layer with a porous structure, and its material includes but is not limited to at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the isolation membrane 103 can be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite membrane.

[0087] Electrolytes The electrolyte has the function of conducting ions between the positive electrode sheet 101 and the negative electrode sheet 102. The state of the electrolyte can be one or more of a gel state, a solid state and a liquid state. In some embodiments, the electrolyte is an electrolyte. The electrolyte plays a role of conducting active ions between the positive electrode sheet 101 and the negative electrode sheet 102. In some embodiments, the electrolyte includes a lithium salt and an organic solvent. The lithium salt can be selected from but is not limited to lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium perchlorate (LiClO 4 ), lithium tetraphenylborate (LiB(C 6 H 5 ) 4 ), lithium methanesulfonate (LiCH 3 SO 3 ), lithium bis(trifluoromethanesulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF 3 SO 3), lithium bis(trifluoromethylsulfonyl)imide (LiN(SO 2 CF 3 ) 2 、Tris(trifluoromethylsulfonyl)methyllithium(LiC(SO 2 CF 3 ) 3 ), lithium bis(oxalatoborate) (LiBOB) and lithium difluorophosphate (LiPO 2 F 2 ) in one or more. For example, the lithium salt is selected from LiPF 6 The organic solvent may be a carbonate compound, a carboxylate compound, an ether compound, a nitrile compound, other organic solvents or a combination thereof. Examples of carbonate compounds include, but are not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or combinations thereof.

[0088] An embodiment of the present application further provides a method for preparing a negative electrode material, the method can achieve filling of carbon material in porous silicon, the method comprising: S10: performing a first heat treatment on the silicon-oxygen precursor material to obtain an intermediate product.

[0089] In some embodiments, the temperature of the first heat treatment is 550° C. to 1250° C. For example, the temperature of the first heat treatment can be 550° C., 650° C., 750° C., 850° C., 950° C., 970° C., 980° C., 1050° C., 1150° C., 1250° C., or any value within the range formed by any two of the above values.

[0090] In some embodiments, the first heat treatment time is 2 h to 18 h. For example, the first heat treatment time can be 2 h, 4 h, 5 h, 6 h, 8 h, 10 h, 15 h, 18 h, or any value within the range of any two of the above values.

[0091] In some embodiments, the heating rate of the first heat treatment is 1°C / min to 20°C / min. For example, the heating rate of the first heat treatment can be 1°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, 13°C / min, 15°C / min, 18°C / min, 20°C / min, or any value within the range formed by any two of the above values.

[0092] In some embodiments, the first heat treatment is performed under an inert gas atmosphere, and the inert gas includes at least one of argon, nitrogen, and helium.

[0093] S20: mixing and reacting the intermediate product with an etching solution, wherein the etching solution includes one or more of an etchant, a surfactant and a flocculant, to obtain a silicon material precursor.

[0094] In some embodiments, the mass ratio of the intermediate product to the etching solution is 1:(3-20). For example, the mass ratio of the intermediate product to the etching solution can be 1:3, 1:5, 1:10, 1:15, 1:20, or any value within the range of any two of the above values.

[0095] In some embodiments, the mass percentage of the etchant in the etching solution is 10% to 80%. For example, the mass percentage of the etchant in the etching solution can be 10%, 30%, 45%, 65%, 80%, or any value within the range formed by any two of the above values.

[0096] In some embodiments, the etchant includes at least one of hydrochloric acid, nitric acid, hydrofluoric acid, ammonium bifluoride, sodium fluoride, and ammonium fluoride.

[0097] In some embodiments, the etching reaction time is 0.5 h to 10 h. For example, the etching reaction time can be 0.5 h, 1 h, 1.5 h, 2 h, 3 h, 5 h, 7 h, 8 h, 9 h, 10 h, or any value within the range formed by any two of the above values.

[0098] In some embodiments, the temperature of the etching reaction is less than or equal to 30° C. For example, the temperature of the etching reaction can be 30° C., 25° C., 20° C., 15° C., 10° C., or any value within the range formed by any two of the above values.

[0099] S30: Mix the silicon material precursor with the first gas-phase carbon source and the inert gas, wherein the flow rate of the first gas-phase carbon source is 0.5 L / min to 15 L / min, and the flow rate of the inert gas is 1.5 L / min to 25 L / min; perform a second heat treatment, wherein the temperature of the second heat treatment is 600 ℃ to 1150 ℃, and the time of the second heat treatment is 0.5 h to 24 h; and obtain a silicon-carbon material precursor.

[0100] For example, the flow rate of the first gaseous carbon source can be 0.5 L / min, 2 L / min, 3 L / min, 5 L / min, 8.5 L / min, 10 L / min, 12 L / min, 15 L / min, or any value within the range formed by any two of the above values. The flow rate of the inert gas can be 1.5 L / min, 4 L / min, 6 L / min, 8 L / min, 10 L / min, 15 L / min, 20 L / min, 25 L / min, or any value within the range formed by any two of the above values. The temperature of the second heat treatment can be 600°C, 700°C, 750°C, 780°C, 800°C, 850°C, 1000°C, 1150°C, or any value within the range formed by any two of the above values. The time of the second heat treatment can be 0.5 h, 3 h, 5 h, 7 h, 10 h, 15 h, 18 h, 22 h, 24 h or any value within the range formed by any two of the above values.

[0101] A certain flow of gaseous carbon source is introduced, and after a certain period of heat preservation, the carbon source undergoes thermal cracking reaction. By controlling the concentration and temperature of the carbon source, the deposition rate of the carbon material inside the silicon material precursor can be changed. When the concentration of the carbon source is high, the carbon deposition is accelerated, which will block some of the internal pores, resulting in some pores not being filled.

[0102] In some embodiments, the heating rate of the second heat treatment is 1°C / min to 30°C / min. For example, the heating rate of the second heat treatment can be 1°C / min, 3°C / min, 5°C / min, 8°C / min, 12°C / min, 16°C / min, 20°C / min, 25°C / min, 30°C / min, or any value within the range formed by any two of the above values.

[0103] In some embodiments, the first gas-phase carbon source includes at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, and liquefied gas.

[0104] In some embodiments, the inert gas includes at least one of argon, nitrogen, and helium.

[0105] In some embodiments, the above process is performed in a fluidized bed apparatus.

[0106] S40: mixing the silicon-carbon material precursor with the second gas-phase carbon source and the inert gas, and performing a third heat treatment to obtain a negative electrode material.

[0107] In some embodiments, the temperature of the third heat treatment is 400° C. to 1050° C. For example, the temperature of the third heat treatment can be 400° C., 500° C., 600° C., 700° C., 750° C., 780° C., 800° C., 850° C., 950° C., 1050° C., or any value within the range formed by any two of the above values.

[0108] In some embodiments, the third heat treatment time is 1 h to 24 h. For example, the third heat treatment time can be 1 h, 3 h, 6 h, 10 h, 15 h, 20 h, 24 h, or any value within the range of any two of the above values.

[0109] In some embodiments, the heating rate of the third heat treatment is 1°C / min to 25°C / min. For example, the heating rate of the third heat treatment can be 1°C / min, 3°C / min, 5°C / min, 10°C / min, 15°C / min, 20°C / min, 25°C / min, or any value within the range formed by any two of the above values.

[0110] In some embodiments, the flow rate of the second gas-phase carbon source is 0.1 L / min to 10 L / min. For example, the flow rate of the second gas-phase carbon source can be 0.1 L / min, 1 L / min, 1.5 L / min, 2.5 L / min, 3 L / min, 4.5 L / min, 5.5 L / min, 7 L / min, 9 L / min, 10 L / min, or any value within the range formed by any two of the above values.

[0111] In some embodiments, the second gas-phase carbon source includes at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, pyrrole, and acetonitrile.

[0112] In some embodiments, the inert gas includes at least one of argon, nitrogen, and helium.

[0113] In some embodiments, the above process is carried out in a horizontal rotary kiln apparatus.

[0114] The preparation method of the negative electrode material provided in the present application is to prepare the material precursor by an etching method, deposit the carbon material inside the silicon material precursor by chemical vapor deposition and reserve holes, and also wrap the surface of the silicon-carbon precursor with a dense carbon layer by chemical vapor deposition, and finally form the negative electrode material. On the one hand, a fluidized bed is used for chemical vapor deposition, the carbon source material is blown up with gas, and then the carbon source penetrates or is adsorbed into the hole and cracked and then deposits carbon, which is conducive to internal carbon deposition. By controlling the carbon deposition rate of the carbon source inside the material, the carbon material can be deposited inside the material while reserving a part of the holes, thereby adjusting the porosity of the negative electrode material, which is conducive to alleviating the volume expansion of silicon. On the other hand, the use of a horizontal rotary kiln for chemical vapor deposition is conducive to carbon coating on the outer surface of the material, so that a dense carbon coating layer is formed on the surface of the material, which can effectively reduce the electrolyte from directly penetrating into the particles of the negative electrode material through the pore structure, reducing the side reactions of the electrolyte and silicon particles, and improving the cycle performance. The reserved internal pores and the dense carbon layer wrapping on the surface can not only reduce the expansion rate of the negative electrode material, which is beneficial to the formation of a stable solid electrolyte film on the surface of the negative electrode material, but also help to improve the material stability, thereby improving the electrochemical performance of the negative electrode material.

[0115] One embodiment of the present application also provides another method for preparing a negative electrode material, which can achieve filling of silicon material in porous carbon. The preparation method includes: S100: subjecting the carbon source precursor material to a first heat treatment, and then activating and purifying it to obtain a porous carbon material.

[0116] In some embodiments, the temperature of the first heat treatment is 500° C. to 1250° C. For example, the temperature of the first heat treatment can be 500° C., 550° C., 650° C., 750° C., 850° C., 950° C., 970° C., 980° C., 1050° C., 1150° C., 1250° C., or any value within the range formed by any two of the above values.

[0117] In some embodiments, the first heat treatment time is 2 h to 18 h. For example, the first heat treatment time can be 2 h, 4 h, 5 h, 6 h, 8 h, 10 h, 15 h, 18 h, or any value within the range of any two of the above values.

[0118] In some embodiments, the heating rate of the first heat treatment is 1°C / min to 20°C / min. For example, the heating rate of the first heat treatment can be 1°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, 13°C / min, 15°C / min, 18°C / min, 20°C / min, or any value within the range formed by any two of the above values.

[0119] In some embodiments, the first heat treatment is performed under an inert gas atmosphere, and the inert gas includes at least one of argon, nitrogen, and helium.

[0120] In some embodiments, activation comprises steam activation, CO 2 At least one of activation and alkali activation. In some embodiments, the activation temperature is 600°C to 1200°C. For example, the activation temperature can be 600°C, 650°C, 750°C, 850°C, 950°C, 970°C, 980°C, 1050°C, 1150°C, 1200°C, or any value within the range formed by any two of the above values.

[0121] In some embodiments, the activation time is 2 h to 40 h. For example, it can be 2 h, 6 h, 8 h, 12 h, 15 h, 19 h, 25 h, 30 h, 35 h, 40 h, or any value within the range formed by any two of the above values.

[0122] In some embodiments, the purification includes acid washing, and the acid solution used for the acid washing includes at least one of hydrochloric acid, nitric acid, hydrofluoric acid, perchloric acid, acetic acid, phosphoric acid, carbonic acid, formic acid and propionic acid.

[0123] In some embodiments, the purification time is 2 h to 20 h. For example, the purification time can be 2 h, 6 h, 8 h, 12 h, 15 h, 19 h, 20 h, or any value within the range formed by any two of the above values.

[0124] S200: Mix the porous carbon material with the first gas-phase silicon source and the inert gas, and perform a second heat treatment to obtain a silicon-carbon material precursor.

[0125] In some embodiments, the first vapor-phase silicon source includes at least one of monosilane, disilane, and trisilane.

[0126] In some embodiments, the inert gas includes nitrogen, argon, hydrogen, helium, krypton, xenon, radon, and a mixture thereof with hydrogen.

[0127] In some embodiments, the flow rate of the first gas-phase silicon source is 0.5 L / min to 50 L / min. For example, the flow rate of the first gas-phase silicon source can be 0.5 L / min, 2 L / min, 3 L / min, 5 L / min, 8.5 L / min, 10 L / min, 12 L / min, 15 L / min, 25 L / min, 35 L / min, 40 L / min, 50 L / min, or any value within the range formed by any two of the above values.

[0128] In some embodiments, the flow rate of the inert gas is 2 L / min to 80 L / min. For example, the flow rate of the inert gas can be 2 L / min, 4 L / min, 6 L / min, 8 L / min, 10 L / min, 15 L / min, 20 L / min, 25 L / min, 35 L / min, 40 L / min, 55 L / min, 60 L / min, 70 L / min, 80 L / min, or any value within the range formed by any two of the above values.

[0129] In some embodiments, the temperature of the second heat treatment is 300° C. to 700° C. For example, the temperature of the second heat treatment can be 300° C., 350° C., 400° C., 450° C., 500° C., 550° C., 600° C., 700° C., or any value within the range formed by any two of the above values.

[0130] In some embodiments, the second heat treatment time is 0.5 h to 24 h. For example, the second heat treatment time can be 0.5 h, 3 h, 5 h, 7 h, 10 h, 15 h, 18 h, 22 h, 24 h, or any value within the range of any two of the above values.

[0131] In some embodiments, the above S200 is performed in a fluidized bed apparatus.

[0132] S300: mixing a silicon-carbon material precursor with a carbon source and an inert gas, wherein the carbon source includes one or more of a first gas-phase carbon source, a liquid-phase carbon source and a solid-phase carbon source, the flow rate of the first gas-phase carbon source is 0.5 L / min to 15 L / min, and the flow rate of the inert gas is 1.5 L / min to 25 L / min; performing a third heat treatment, the temperature of the third heat treatment is 600°C to 1150°C, and the time of the third heat treatment is 0.5 h to 24 h; obtaining a silicon-carbon material intermediate.

[0133] For example, the flow rate of the first gaseous carbon source can be 0.5 L / min, 2 L / min, 3 L / min, 5 L / min, 8.5 L / min, 10 L / min, 12 L / min, 15 L / min, or any value within the range formed by any two of the above values. The flow rate of the inert gas can be 1.5 L / min, 4 L / min, 6 L / min, 8 L / min, 10 L / min, 15 L / min, 20 L / min, 25 L / min, or any value within the range formed by any two of the above values. The temperature of the third heat treatment can be 600°C, 700°C, 750°C, 780°C, 800°C, 850°C, 1000°C, 1150°C, or any value within the range formed by any two of the above values. The time of the third heat treatment can be 0.5 h, 3 h, 5 h, 7 h, 10 h, 15 h, 18 h, 22 h, 24 h or any value within the range formed by any two of the above values.

[0134] A certain flow of gaseous carbon source is introduced, and after a certain period of heat preservation, the carbon source undergoes thermal cracking reaction. By controlling the concentration and temperature of the carbon source, the deposition rate of the carbon material inside the silicon material precursor can be changed. When the concentration of the carbon source is high, the carbon deposition is accelerated, which will block some of the internal pores, resulting in some pores not being filled.

[0135] In some embodiments, the heating rate of the third heat treatment is 1°C / min to 30°C / min. For example, the heating rate of the third heat treatment can be 1°C / min, 3°C / min, 5°C / min, 8°C / min, 12°C / min, 16°C / min, 20°C / min, 25°C / min, 30°C / min, or any value within the range formed by any two of the above values.

[0136] In some embodiments, the first gas-phase carbon source includes at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, and liquefied gas.

[0137] In some embodiments, the inert gas includes at least one of argon, nitrogen, and helium.

[0138] In some embodiments, the above S300 is performed in a horizontal rotary kiln device.

[0139] S400: mixing the silicon-carbon material intermediate with the second gas-phase carbon source and the inert gas, and performing a fourth heat treatment to obtain a negative electrode material.

[0140] In some embodiments, the temperature of the fourth heat treatment is 400° C. to 850° C. For example, the temperature of the fourth heat treatment can be 400° C., 450° C., 500° C., 550° C., 600° C., 650° C., 700° C., 800° C., 850° C., or any value within the range formed by any two of the above values.

[0141] In some embodiments, the fourth heat treatment lasts for 1 to 24 hours. For example, the fourth heat treatment lasts for 1 hour, 3 hours, 6 hours, 10 hours, 15 hours, 20 hours, 24 hours, or any value within the range of any two of the above values.

[0142] In some embodiments, the heating rate of the fourth heat treatment is 1°C / min to 25°C / min. For example, the heating rate of the fourth heat treatment can be 1°C / min, 3°C / min, 5°C / min, 10°C / min, 15°C / min, 20°C / min, 25°C / min, or any value within the range formed by any two of the above values.

[0143] In some embodiments, the flow rate of the second gas-phase carbon source is 0.1 L / min to 10 L / min. For example, the flow rate of the second gas-phase carbon source can be 0.1 L / min, 1 L / min, 1.5 L / min, 2.5 L / min, 3 L / min, 4.5 L / min, 5.5 L / min, 7 L / min, 9 L / min, 10 L / min, or any value within the range formed by any two of the above values.

[0144] In some embodiments, the second gas-phase carbon source includes at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, pyrrole, and acetonitrile.

[0145] In some embodiments, the inert gas includes at least one of argon, nitrogen, and helium.

[0146] In some embodiments, the above S400 is performed in a horizontal rotary kiln device.

[0147] The preparation method of the negative electrode material provided in the present application is to prepare a porous carbon material by an activation method, deposit silicon material inside the porous carbon material by chemical vapor deposition and reserve holes, and also wrap a dense carbon layer on the surface of the silicon-carbon precursor by chemical vapor deposition, and finally form a negative electrode material. On the one hand, a fluidized bed is used for chemical vapor deposition, the carbon source material is blown up with gas, and then the silicon source gas penetrates or is adsorbed into the hole and cracked and deposited silicon, which is conducive to internal silicon deposition. By controlling the deposition rate of the silicon source inside the material, the silicon material can be deposited inside the carbon material while reserving a part of the holes, thereby adjusting the porosity of the negative electrode material, which is conducive to alleviating the volume expansion of silicon. On the other hand, the use of a horizontal rotary furnace for chemical vapor deposition is conducive to carbon coating on the outer surface of the material, so that a dense carbon coating layer is formed on the surface of the material, which can effectively reduce the electrolyte from directly penetrating into the particles of the negative electrode material through the pore structure, reducing the side reactions caused by the contact between the electrolyte and the silicon particles, and improving the cycle performance. The reserved internal pores and the dense carbon layer wrapping on the surface can not only reduce the expansion rate of the negative electrode material, which is beneficial to the formation of a stable solid electrolyte film on the surface of the negative electrode material, but also help to improve the material stability, thereby improving the electrochemical performance of the negative electrode material.

[0148] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0149] Embodiment 1: A negative electrode material, the preparation method of which comprises: S1, put the silicon oxide precursor material SiOx (0.5<x<2) into an atmosphere furnace, and heat it to 950 ℃ at a heating rate of 3 ℃ / min under the protection of argon atmosphere, keep it at this temperature for 5 h, and then cool it to obtain the intermediate product.

[0150] S2, putting the intermediate product into an etching solution, the mass ratio of the intermediate product to the etching solution is 1:10, the etching solution is a hydrofluoric acid solution with a mass content concentration of 30%, the etching reaction time is 1.5 h, the etching reaction temperature is controlled at 25 ° C, and a silicon material precursor is obtained after washing and drying.

[0151] S3, 1 kg of silicon material precursor was placed in a vertical fluidized bed device, the air therein was replaced with an inert gas, 3 L / min of argon was introduced as a power gas, and after heating to 700 °C at a heating rate of 3 °C / min, propane with a gas flow rate of 2 L / min was introduced as a carbon source gas. After keeping the temperature for 3 h, the silicon-carbon material precursor was obtained by cooling.

[0152] S4, put 500 g of silicon-carbon material precursor into a horizontal rotary furnace, replace the air therein with inert gas, and heat it to 700 °C at a heating rate of 3 °C / min under the protection of argon atmosphere. Then, introduce acetylene as a carbon source gas with a gas flow rate of 2.5 L / min. After keeping warm for 3 h, cool it to obtain the negative electrode material.

[0153] Embodiment 2: S1, put silicon monoxide into an atmosphere furnace, under the protection of argon atmosphere, heat it to 970 ° C at a heating rate of 3 ° C / min, keep it at this temperature for 4 h, and then cool it to obtain an intermediate product.

[0154] S2, putting the intermediate product into an etching solution, the mass ratio of the intermediate product to the etching solution is 1:5, the etching solution is a hydrofluoric acid solution with a mass content concentration of 45%, the etching reaction time is 1.0 h, the etching reaction temperature is controlled at 20 ° C, and a silicon material precursor is obtained after washing and drying.

[0155] S3, 1 kg of silicon material precursor was placed in a vertical fluidized bed device, the air therein was replaced with an inert gas, 4 L / min of argon was introduced as a power gas, and after heating to 780 °C at a heating rate of 3 °C / min, propane with a gas flow rate of 3 L / min was introduced as a carbon source gas, and after keeping warm for 3 h, the silicon-carbon material precursor was obtained by cooling.

[0156] S4, put 500 g of silicon-carbon material precursor into a horizontal rotary furnace, replace the air therein with inert gas, and heat it to 750 °C at a heating rate of 3 °C / min under the protection of argon atmosphere. Then, introduce acetylene as a carbon source gas with a gas flow rate of 3 L / min. After keeping warm for 3 h, cool it to obtain the negative electrode material.

[0157] Embodiment 3: S1, put the silicon oxide precursor material SiOx (0.5<x<2) into an atmosphere furnace, and heat it to 970 ℃ at a heating rate of 3 ℃ / min under the protection of argon atmosphere, keep it at this temperature for 6 hours, and then cool it to obtain the intermediate product.

[0158] S2, putting the intermediate product into an etching solution, the mass ratio of the intermediate product to the etching solution is 1:10, the etching solution is a hydrofluoric acid solution with a mass content concentration of 45%, the etching reaction time is 1.5 h, the etching reaction temperature is controlled at 20 ° C, and a silicon material precursor is obtained after washing and drying.

[0159] S3, 1 kg of silicon material precursor was placed in a vertical fluidized bed device, the air therein was replaced with an inert gas, 4 L / min of argon was introduced as a power gas, and after heating to 800 °C at a heating rate of 3 °C / min, propane with a gas flow rate of 3 L / min was introduced as a carbon source gas. After keeping warm for 3 h, the silicon-carbon material precursor was obtained by cooling.

[0160] S4, put 500 g of silicon-carbon material precursor into a horizontal rotary furnace, replace the air therein with inert gas, and heat it to 780 °C at a heating rate of 3 °C / min under the protection of argon atmosphere. Then, introduce acetylene as a carbon source gas with a gas flow rate of 4.5 L / min. After keeping warm for 3 h, cool it to obtain the negative electrode material.

[0161] Embodiment 4: S1, put the silicon oxide precursor material SiOx (0.5<x<2) into an atmosphere furnace, and heat it to 980 ℃ at a heating rate of 3 ℃ / min under the protection of argon atmosphere, keep it at this temperature for 8 h, and then cool it to obtain the intermediate product.

[0162] S2, putting the intermediate product into an etching solution, the mass ratio of the intermediate product to the etching solution is 1:15, the etching solution is a hydrofluoric acid solution with a mass content concentration of 65%, the etching reaction time is 1.0 h, the etching reaction temperature is controlled at 20 ° C, and a silicon material precursor is obtained after washing and drying.

[0163] S3, 1 kg of silicon material precursor was placed in a vertical fluidized bed device, the air therein was replaced with an inert gas, 4 L / min of argon was introduced as a power gas, and after heating to 850 °C at a heating rate of 3 °C / min, propane with a gas flow rate of 3 L / min was introduced as a carbon source gas, and after keeping warm for 3 h, the silicon-carbon material precursor was obtained by cooling.

[0164] S4, put 500 g of silicon-carbon material precursor into a horizontal rotary furnace, replace the air therein with inert gas, and heat it to 800 °C at a heating rate of 3 °C / min under the protection of argon atmosphere. Then, introduce acetylene as a carbon source gas with a gas flow rate of 5.5 L / min. After keeping warm for 3 h, cool it to obtain the negative electrode material.

[0165] Embodiment 5: The difference from Example 1 is that in S4, the heating temperature is adjusted to 750° C. and the carbon source gas is adjusted to propane.

[0166] Embodiment 6: The difference from Example 1 is that in S4, the carbon source gas is adjusted to propane.

[0167] Embodiment 7: The difference from Example 1 is that in S3, the flow rate of the carbon source gas is adjusted to 8.5 L / min; and in S4, the heating temperature is adjusted to 850°C.

[0168] Embodiment 8: The difference from Example 1 is that in S1, the heating temperature is adjusted to 750°C and the holding time is 15 h; in S3, the flow rate of the carbon source gas is adjusted to 15 L / min; and in S4, the heating temperature is adjusted to 850°C.

[0169] Embodiment 9: The difference from Example 1 is that in S1, the heating temperature is adjusted to 1150°C and the holding time is 12 h; in S3, the flow rate of the carbon source gas is adjusted to 10 L / min; and in S4, the heating temperature is adjusted to 1000°C.

[0170] Embodiment 10: The difference from Example 1 is that S3 is not performed, that is, S1, S2 and S4 are performed in the order of steps.

[0171] Embodiment 11: A negative electrode material, the preparation method of which comprises: S1, put the coconut shell into an atmosphere furnace, and carry out the first heat treatment under the protection of argon atmosphere: heat to 950 ℃ at a heating rate of 3 ℃ / min, keep warm for 5 hours, and then carbonize to obtain carbonized material; then put the carbonized material into a rotary kiln, pass water vapor and nitrogen mixed gas (volume ratio 1:100), heat to 850 ℃, activate for 12 hours. After activation, put it into 2 mol / L hydrochloric acid mixed solution for pickling, pickling time 20 hours, and dry to obtain porous carbon material.

[0172] S2, put the porous carbon material into a vertical fluidized bed, replace the air therein with an inert gas, introduce 3 L / min of argon as a power gas and 5 L / min of a silane gas mixture, and perform a second heat treatment: heat to 500 °C at a heating rate of 3 °C / min, keep warm for 8 h, and then cool to obtain a silicon-carbon material precursor.

[0173] S3, continuing on the basis of step 2, 3 L / min of argon is introduced as the power gas to carry out the third heat treatment: heating to 700 °C at a heating rate of 3 °C / min, and then, propane with a gas flow rate of 2 L / min is introduced as the carbon source gas, and after keeping warm for 3 hours, cooling is performed to obtain a silicon-carbon material intermediate.

[0174] S4, put 500 g of the silicon-carbon material intermediate into a horizontal rotary furnace, replace the air therein with an inert gas, and carry out the fourth heat treatment under the protection of an argon atmosphere: heat to 700 °C at a heating rate of 3 °C / min, then introduce acetylene as a carbon source gas at a gas flow rate of 2.5 L / min, keep warm for 3 h, and then cool to obtain the final negative electrode material.

[0175] Embodiment 12: S1, put the fruit shell into an atmosphere furnace, and carry out the first heat treatment under the protection of nitrogen atmosphere: heat to 950 ℃ at a heating rate of 6 ℃ / min, keep warm for 7 hours, and then carbonize to obtain carbonized material; then put the carbonized material into a rotary kiln, pass water vapor and nitrogen mixed gas (volume ratio 1.5:100), heat to 950 ℃, activate for 10 hours. After activation, put it into 5 mol / L hydrochloric acid mixture for pickling, pickling time 18 hours, and dry to obtain porous carbon material.

[0176] S2, put the porous carbon material into a vertical fluidized bed, replace the air therein with an inert gas, introduce 10 L / min of argon as a power gas and 8 L / min of a silane gas mixture, and perform a second heat treatment: heat to 600 °C at a heating rate of 2 °C / min, keep warm for 7 h, and then cool to obtain a silicon-carbon material precursor.

[0177] S3, continuing on the basis of step 2, continue to introduce 3 L / min of argon as the power gas, and carry out the third heat treatment: heat to 600 °C at a heating rate of 3 °C / min, then introduce propane with a gas flow rate of 2 L / min as the carbon source gas, keep warm for 3 hours, and then cool to obtain a silicon-carbon material intermediate.

[0178] S4, put 500 g of the silicon-carbon material intermediate into a horizontal rotary furnace, replace the air therein with an inert gas, and carry out the fourth heat treatment under the protection of an argon atmosphere: heat to 700 °C at a heating rate of 3 °C / min, then introduce acetylene as a carbon source gas at a gas flow rate of 8.5 L / min, keep warm for 3 h, and then cool to obtain the final negative electrode material.

[0179] Embodiment 13: S1, put the apricot shell into an atmosphere furnace, and carry out the first heat treatment under the protection of nitrogen atmosphere: heat to 790 ℃ at a heating rate of 8 ℃ / min, keep warm for 8 hours, and then carbonize to obtain carbonized material; then put the carbonized material into a rotary kiln, pass a mixture of carbon dioxide and nitrogen (volume ratio 5:100), heat to 950 ℃, activate for 19 hours. After activation, put it into a 6 mol / L hydrochloric acid mixture for pickling, pickling for 12 hours, and dry to obtain a porous carbon material.

[0180] S2, put the porous carbon material into a vertical fluidized bed, replace the air therein with an inert gas, introduce 23 L / min of argon as a power gas and 6 L / min of a silane gas mixture, and perform a second heat treatment: heat to 550 °C at a heating rate of 6 °C / min, keep warm for 8 h, and then cool to obtain a silicon-carbon material precursor.

[0181] S3, continuing on the basis of step 2, introducing 12 L / min of 95% argon and 5% hydrogen as power gas, and performing the third heat treatment: heating to 650 °C at a heating rate of 3 °C / min, and then introducing ethylene as a carbon source gas at a gas flow rate of 6 L / min, after keeping warm for 3 hours, cooling to obtain a silicon-carbon material intermediate.

[0182] S4, put 500 g of the silicon-carbon material intermediate into a horizontal rotary furnace, replace the air therein with an inert gas, and carry out the fourth heat treatment under the protection of an argon atmosphere: heat to 680 °C at a heating rate of 1 °C / min, then introduce acetylene as a carbon source gas at a gas flow rate of 9.5 L / min, keep warm for 3 h, and then cool to obtain the final negative electrode material.

[0183] Embodiment 14: S1, put the phenolic resin into an atmosphere furnace, and carry out the first heat treatment under the protection of argon atmosphere: heat to 950 ℃ at a heating rate of 3 ℃ / min, keep warm for 5 hours, then carbonize and polymerize to obtain carbonized material; then mix the carbonized material with KOH (carbonized material: KOH=100:45), heat to 750 ℃, activate for 12 hours. After activation, put it into 9 mol / L hydrochloric acid mixture for pickling, pickling time for 20 hours, and dry to obtain porous carbon material.

[0184] S2, put the porous carbon material into a vertical fluidized bed, replace the air therein with an inert gas, introduce 23 L / min of nitrogen as a power gas and 15 L / min of a silane gas mixture, and perform a second heat treatment: heat to 400 °C at a heating rate of 3 °C / min, keep warm for 10 h, and then cool to obtain a silicon-carbon material precursor.

[0185] S3, continuing on the basis of step 2, introducing 13 L / min of argon as the power gas, and performing the third heat treatment: heating to 600 °C at a heating rate of 3 °C / min, and then introducing propane with a gas flow rate of 12 L / min as the carbon source gas, keeping warm for 3 h, and then cooling to obtain a silicon-carbon material intermediate.

[0186] S4, put 500 g of the silicon-carbon material intermediate into a horizontal rotary furnace, replace the air therein with an inert gas, and carry out the fourth heat treatment under the protection of an argon atmosphere: heat to 700 °C at a heating rate of 2 °C / min, then introduce acetylene as a carbon source gas at a gas flow rate of 1.5 L / min, keep warm for 3 h, and then cool to obtain the final negative electrode material.

[0187] Embodiment 15: The difference from Example 11 is that in S4, the temperature of the fourth heat treatment is adjusted to 750° C., and the carbon source gas is adjusted to propane.

[0188] Embodiment 16: The difference from Example 11 is that in S4, the carbon source gas is adjusted to propane.

[0189] Embodiment 17: The difference from Example 11 is that in S3, the flow rate of the carbon source gas is adjusted to 8.5 L / min; in S4, the temperature of the fourth heating is adjusted to 850°C.

[0190] Embodiment 18: The difference from Example 11 is that in S1, the temperature of the first heat treatment is adjusted to 750°C and the holding time is 15h, in S3, the flow rate of the carbon source gas is adjusted to 15 L / min; in S4, the temperature of the fourth heating is adjusted to 850°C.

[0191] Embodiment 19: The difference from Example 11 is that in S1, the temperature of the first heat treatment is adjusted to 1150°C and the holding time is 12 h, in S3, the flow rate of the carbon source gas is adjusted to 10 L / min; in S4, the temperature of the fourth heating is adjusted to 800°C.

[0192] Embodiment 20: The difference from Example 11 is that S3 is not performed, that is, S1, S2 and S4 are performed in the order of steps.

[0193] Embodiment 21: S1, the fruit shell was subjected to the first heat treatment: carbonization treatment was carried out at 500 ℃ for 5 h, and then the carbonization product was pickled with 5 mol / L hydrochloric acid for 4 h. After drying, it was placed in a heat treatment furnace and a mixture of water vapor and nitrogen (volume ratio 1:80) was introduced for activation treatment. The treatment temperature was 800 ℃ and the time was 12 h, and a carbon matrix with an average pore size of 2.1 nm was obtained.

[0194] S2, placing the carbon substrate in a chemical vapor deposition (CVD) device, introducing silane into the CVD device at a rate of 18 L / min, controlling the volume concentration of silane to be 20%, and then performing a second heat treatment: raising the temperature to 500 °C, performing a vapor deposition reaction for 4 hours, and obtaining a core.

[0195] S3, the core and the phenolic resin are mixed in a mass ratio of 50:15, and then the mixed materials are placed in a high-temperature box furnace, nitrogen is introduced, and the third heat treatment is performed: heat treatment is performed at 720 °C for 2 h.

[0196] S4, crushing, sieving, and then classifying the obtained sample to obtain a negative electrode material with a carbon layer on the surface.

[0197] The physical and electrochemical properties of the negative electrode materials obtained in the above examples 1-21 were tested, and the testing methods were as follows: 1. Specific surface area test of materials: Using the ASAP2460 surface area and pore size analyzer from Micromeritics, USA, at liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its specific surface area and other characteristics. Combined with the law of change of adsorption amount with relative pressure during adsorption, various models can be fitted to calculate the specific surface area.

[0198] 2. Total pore volume test of materials: The test was carried out using ASAP2460 equipment from Micromeritics, USA. The pore volume V was calculated using the BJH Desorption cumulative volume of pores model in the pore size range of 17 Å-3000 Å.

[0199] 3. Micropore and mesopore analysis of materials: Micromeretics ASAP 2460 is used for micropore and mesopore analysis. At liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its pore size and other characteristics. Combined with the law of the change of adsorption amount with relative pressure during the adsorption process, multiple models can be fitted to calculate the pore size. The report generated by the software uses the density functional theory (abbreviated as DFT) method to calculate the pore size distribution, total pore volume and pore volume within a certain range.

[0200] 4. Average pore size test of negative electrode materials: Take an appropriate amount of sample particles and randomly measure the diameters of 20 holes under a transmission electron microscope (TEM). For irregular holes, calculate the sum of the longest side and the shortest side divided by 2, and calculate the average pore size of the 20 holes.

[0201] 5. Particle size test of negative electrode materials: The particle size test method refers to GB / T 19077-2016. It can be conveniently measured with a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.

[0202] 6. Compaction density test of negative electrode materials: Using the CARVER 4350.22 powder compaction density meter from American McNally, a sample of specified mass is placed in a mold and subjected to a pressure of 1.0 T. After maintaining the pressure for 30 s, the pressure is removed to test its thickness and the compaction density is calculated. The specific operation method is to place a certain mass of powder sample in a metal sleeve, and the ratio of the mass of the sample to the compacted volume after maintaining it under a certain pressure for a certain period of time is calculated.

[0203] 7. Test of oxygen content and carbon content of negative electrode materials: The oxygen content was measured by using the German Verder oxygen, nitrogen and hydrogen element analyzer (ONH2000) with reference to the national standard "Determination of oxygen content of steel by pulse heat treatment inert gas melting-infrared absorption method. GB / T 11261-2006". The carbon content was tested by using the Mettler TGA-DSC1 synchronous thermal analyzer with reference to the national standard "Test method for weight loss and residual amount of thermogravimetric analyzer GB / T 27761-2011".

[0204] 8. Test of the average particle size of primary particles of silicon materials: The material was sectioned using a FIB-TEM focused ion beam scanning transmission electron microscope Helios G4 PFIB HXe, and the sizes of 20 primary particles were measured in the TEM. The size of irregular particles was calculated by dividing the sum of the longest side and the shortest side by 2. The average value of the 20 particles was the average particle size of the primary particles.

[0205] 9. Test of the grain size of silicon material on the (111) crystal plane: The XRD pattern of the sample was measured by X-ray diffractometer, and the half-peak width of the diffraction peak on the (111) crystal plane of the sample and the corresponding Bragg angle were obtained by jade software. The Scherrer formula D = Kγ / B cos θ The grain size on the (111) crystal plane of silicon material is calculated.

[0206] 10. Porosity test of negative electrode materials: The mercury intrusion method is a method for calculating porosity by measuring the pressure change of mercury in the pores of the material. This method uses the AutoPore IV 9500 high-performance fully automatic mercury intrusion instrument of Micromeritics Instruments to press mercury into the pores of the material. Based on the volume change and pressure change of mercury, the porosity and pore distribution can be calculated.

[0207] 11. Electrochemical performance test: A negative electrode slurry is prepared according to a mass ratio of 70:15:15 of negative electrode material, conductive carbon black, and LA133 binder, coated on copper foil, and dried to form a negative electrode sheet. A metal lithium sheet is used as the counter electrode, and the first button battery is assembled in a glove box filled with argon. A negative electrode slurry is prepared according to a mass ratio of 92:2:2:2:2 of negative electrode active material, conductive carbon (Super-P), conductive graphite (KS-6), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), and the negative electrode slurry is coated on copper foil, and dried to form a negative electrode sheet. The negative electrode active material is a mixture of the negative electrode material of the present application and graphite, and the specific capacity of the mixture is 480 mAh / g, wherein the proportion of the negative electrode material and graphite is determined by the first reversible specific capacity of the two and the capacity required for the two to be matched. A metal lithium sheet is used as the counter electrode, and the second button battery is assembled in a glove box filled with argon.

[0208] (1) Test method for first discharge specific capacity and first coulombic efficiency (ICE): the first button cell is charged and discharged at a current density of 0.01 C in the charge and discharge range of 0.005 V to 1.5 V to obtain the first discharge specific capacity and first coulombic efficiency of the button cell; (2) Charge rate test: In the charge and discharge range of 0.005 V to 1.5 V, first, the first button cell was charged and discharged at a current density of 0.1 C, and the discharge capacity was measured as Q1; then the button cell was charged at a charging current of 0.1 C, and the button cell was discharged at a discharge current of 2.0 C, and the discharge capacity was measured as Q2. Q2 / Q1 was used to measure the fast charging performance of the material; (3) High temperature performance test: The first button cell was charged and discharged at a current density of 0.1 C in the charge and discharge range of 0.005 V to 1.5 V. The test condition was a constant temperature box at 45 °C. The capacity retention rate was measured after 20 cycles, that is, capacity retention rate = 20th cycle discharge specific capacity / 1st cycle discharge specific capacity * 100%; (4) Test of capacity retention rate and electrode thickness expansion rate after 50 cycles: The second button cell was charged and discharged 50 times at a current density of 0.25 C in the charge and discharge range of 0.005 V to 5 V to obtain the capacity retention rate and electrode thickness expansion rate after 50 cycles of the battery. Capacity retention rate = 50th cycle discharge capacity / 1st cycle discharge capacity * 100%.

[0209] The test results of Examples 1-10 are shown in Tables 1 and 2, and the test results of Examples 11-21 are shown in Tables 3 and 4.

[0210] Taking Example 1 as an example, the above test results are further described in conjunction with the accompanying drawings. Figure 3 and Figure 4In the dQ / dV-V curves under the first charge and discharge conditions and the second charge and discharge conditions, within the preset interval, the M value is 12.6, the N value is 7.7, and the N / M is about 0.61, which falls within the preset range. Figure 5 The surface of the negative electrode material in the embodiment of the present application is relatively smooth, and no cracks are observed. Figure 6 , the negative electrode material of the present embodiment has a dense carbon layer on its surface, and holes are reserved inside (indicated by arrows). Figure 7 In the XRD spectrum of the negative electrode material of the present embodiment, the three strong peaks at 28.4°, 47.3° and 56.1° correspond to the three strong peaks of silicon (JCPDS No. 27-1402), and there is basically no impurity phase. The grain size of the silicon material on the (111) crystal plane is calculated according to the Scherrer formula, which is 3.7 nm in Example 1. Please refer to Figure 8 The negative electrode material of the present application example has excellent cycle performance. After 50 cycles at 0.25C current, the capacity retention rate of Example 1 is 91.4%. Please refer to Fig. 9 The negative electrode material of the embodiment of the present application has a higher charge-discharge specific capacity and first coulombic efficiency.

[0211] Table 1. Test results of physical and chemical parameters of negative electrode materials of Examples 1-10 of the present application Table 2. Electrochemical performance test results of negative electrode materials of Examples 1-10 of the present application Table 3. Test results of physical and chemical parameters of negative electrode materials of Examples 11-21 of the present application Table 4. Electrochemical performance test results of negative electrode materials of Examples 11-21 of the present application Under the preparation process conditions of the present application, the negative electrode materials of Examples 1-9 and Examples 11-19 are improved by carbon coating, optimized silicon material structure, reserved internal pores, and composite structure construction, and the value of N / M is controlled to meet the following conditions: 0.35≤N / M≤0.85. On the one hand, the formation of crystalline lithium-silicon alloy generated by the reaction of silicon and lithium in the negative electrode material is reduced, and the volume expansion of the silicon material during the cycle is alleviated, which is conducive to maintaining the stability of the structure of the negative electrode material, so that the secondary battery using the negative electrode material has a good capacity retention rate and cycle life; on the other hand, it can avoid the electrochemical sintering of the silicon negative electrode during the lithiation / delithiation process to form large particles, thereby enhancing the lithium deintercalation kinetics advantage of the negative electrode material, improving the rate performance and high-temperature storage performance of the negative electrode material, and improving the overall electrochemical performance of the secondary battery using the negative electrode material.

[0212] Compared with Example 1, Example 10 reduces one step of the carbon material deposition reaction step, which affects the coating effect of the subsequent carbon coating layer. The N / M value of the obtained negative electrode material exceeds the preset range, and the cycle stability, rate performance and high-temperature storage performance of the secondary battery using the negative electrode material are significantly deteriorated.

[0213] Compared with Example 11, Example 20 reduces one reaction step of the carbon material, which affects the coating effect of the carbon coating layer. The N / M value of the obtained negative electrode material exceeds the preset range, and the cycle stability, rate performance and high-temperature storage performance of the secondary battery using the negative electrode material are significantly deteriorated.

[0214] Compared with Example 11, Example 21 is a negative electrode material prepared by conventional chemical vapor deposition. The N / M value of the obtained negative electrode material exceeds the preset range, and the cycle stability, rate performance and high-temperature storage performance of the secondary battery using this negative electrode material are significantly deteriorated.

[0215] In summary, the present application provides a negative electrode material with reserved internal pores and a dense carbon layer wrapped on the surface by improving the preparation process, so that its N / M value is within a preset range, which can not only reduce the expansion rate of the negative electrode material, which is conducive to the formation of a stable solid electrolyte film on the surface of the negative electrode material, but also help to improve the material stability, thereby improving the electrochemical performance of the negative electrode material.

[0216] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes carbon material and silicon material; Using metallic lithium as a reference electrode and a counter electrode, and the negative electrode material as a working electrode, a button half-cell charge and discharge test is performed under a first charge and discharge condition and a second charge and discharge condition, wherein the discharge cut-off voltage of the first charge and discharge condition is 0.005 V, and the charge cut-off voltage is 1.5 V, and the discharge cut-off voltage of the second charge and discharge condition is 0.025 V, and the charge cut-off voltage is 1.5 V, and a dQ / dV-V curve is obtained; Under the first charge and discharge condition, the maximum value of the dQ / dV-V curve within 0.4 V to 0.5 V is M, and under the second charge and discharge condition, the maximum value of the dQ / dV-V curve within 0.4 V to 0.5 V is N, and M and N satisfy:

2. The negative electrode material according to claim 1, characterized in that The average particle size of the primary particles of the silicon material is 0.1 nm to 25 nm.

3. The negative electrode material according to claim 1, characterized in that The size of the grains of the silicon material on the (111) crystal plane is less than or equal to 10 nm.

4. The negative electrode material according to claim 1, characterized in that The negative electrode material has pores, and the negative electrode material satisfies at least one of the following conditions: (1) The porosity of the negative electrode material is 0.02% to 10%; (2) The average pore size of the negative electrode material is 0.5 nm to 50 nm; (3) The total pore volume of the negative electrode material is 0.001 cm 3 / g to 0.1 cm 3 / g.

5. The negative electrode material according to claim 1, characterized in that The silicon material satisfies at least one of the following conditions: (1) The silicon material includes one or more of amorphous silicon, crystalline silicon, and a composite of crystalline silicon and amorphous silicon; (2) The silicon material includes one or both of silicon oxide and silicon alloy; (3) The morphology of the silicon material particles includes one or more of point-shaped, spherical, ellipsoidal and flake-shaped; (4) The purity of the silicon material is greater than or equal to 99%.

6. The negative electrode material according to claim 1, characterized in that The carbon material includes one or more of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers and graphene.

7. The negative electrode material according to claim 1, characterized in that After the silicon material is removed from the negative electrode material, at least one of the following conditions is met: (1) Its total pore volume is greater than or equal to 0.35 cm 3 / g; (2) The volume proportion of its mesopores in all its pores is greater than or equal to 65%, and the pore size of the mesopores is 2 nm to 50 nm; (3) The volume proportion of its micropores in all pores is greater than or equal to 60%, and the pore diameter of the micropores is less than 2 nm; (4) Its specific surface area is greater than or equal to 100 m 2 / g.

8. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following conditions: (1) The median particle size Dv50 of the negative electrode material is 0.2 µm to 20 µm; (2) The specific surface area of ​​the negative electrode material is 0.1 m 2 / g to 10 m 2 / g; (3) The compacted density of the negative electrode material powder is 0.8 g / cm 3 Up to 1.5 g / cm 3 ; (4) Based on the mass of the negative electrode material, the mass proportion of carbon in the negative electrode material is 10% to 60%; (5) Based on the mass of the negative electrode material, the mass proportion of oxygen in the negative electrode material is less than or equal to 5%.

9. The negative electrode material according to claim 1, characterized in that The negative electrode material further includes a coating, which is located at the outermost layer of the negative electrode material, and the coating also satisfies at least one of the following conditions: (1) The coating includes a carbonaceous material, and the carbonaceous material includes one or more of graphene, soft carbon and hard carbon; (2) The coating includes a metal oxide layer, and the material of the metal oxide layer includes one or more of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide and vanadium oxide; (3) The coating includes a nitride layer, and the nitride layer includes one or more of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride and carbon nitride; (4) The coating includes a polymer, and the polymer includes one or more of tannic acid, polyacrylonitrile, polyaniline, polyethylene glycol, polyvinyl alcohol and asphalt; (5) The thickness of the coating is 0.1 nm to 100 nm.

10. A secondary battery, characterized in that: The secondary battery comprises the negative electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method of preparing electrode active material and battery electrode

    CN110783531A

  • Si-SiOx (at) C / graphite negative electrode material and preparation method thereof

    CN115621457A

  • Negative electrode material, secondary battery and electronic device

    CN116053434A

  • Composite negative electrode material, preparation method thereof, secondary battery and electronic device

    CN118335946A

  • Porous silicon carbon composite, method for preparing same, and anode active

    CN118613929A